Comparison of MOSFET Gate Waffle Patterns Based on Specific On-Resistance - P. Vacula; V. Kote; D. Barri; M. Vacula; M. Husak; J. Jakovenko; S. Privitera (Radioengineering, 2019)
This article describes waffle power MOSFET segmentation and defines its analytic models. Although waffle gate pattern is well-known architecture for effective channel scaling without requirements on process modification, no until today precise model considering segmentation of MOSFETs with waffle gate patterns, due to bulk connections, has been there proposed. Two different MOSFET topologies with gate waffle patterns have been investigated and compared with the same on-resistance of a standard MOSFET with finger gate pattern. The first one with diagonal metal interconnections allows reaching more than 40 % area reduction. The second MOSFET with the more simple orthogonal metal interconnections allows saving more than 20 % area. Moreover, new models defining conditions where segmented power MOSFETs with waffle gate patterns occupy less area than the standard MOSFET with finger gate pattern, have been introduced.